The Development of Chinese Gas Pricing – Drivers, Challenges and Implications for Demand - Chen, M (Oxford Institute for Energy Studies, 2014)
The spectacular growth of the Chinese economy since the early 2000s is a phenomenon familiar to all with an interest in the global economy. Clearly its impact on commodity markets in general has been both significant and observable. While China’s consumption of natural gas grew dramatically in the 2000s it was only in the second half of that decade that demand began to significantly outstrip domestic production, requiring pipeline and LNG import infrastructure and supply lines to be put in place. With pipeline imports secured from Myanmar, Turkmenistan and Central Asia and more recently East Siberia, as well as a range of LNG suppliers, China is rapidly becoming ‘connected’ to a portfolio of international supplies. As its demand growth increases, the scale of its import requirements will influence both regional and global trade flow dynamics. The vast geographic extent of China, the dispersion of its several gas producing regions and the location of import pipeline and LNG facilities, relative to centres of consumption, raise the related challenges of providing sufficient connecting pipeline infrastructure and a rational framework for city gate gas prices which reflect border prices and transportation costs. This paper by Michael Chen describes, within the context of China’s continued rapid gas sector development, the evolution and current status of Chinese gas price reform, which establishes city gate benchmark prices, most notably at Shanghai. These provide the basis on which sectoral prices are determined for consumption and well head prices at the various producing regions. The paper also discusses the likely future path of pricing evolution and identifies the likely response of different demand sectors in various regions within China, both to price levels and supply availability. On the OIES Natural Gas Research Programme we frequently acknowledge the increasing importance of understanding the key high growth Asian importing gas markets, and especially their impact on other world regions through competition for supply and price arbitrage. I am therefore delighted to add this paper, which significantly progresses our understanding of this highly important market in its continuing period of growth and transition to our published portfolio.